Pengaruh Profitabilitas, Likuiditas, BOPO dan Struktur Modal Kerja terhadap Nilai Perusahaan Perbankan Syariah. - Annisa Haznun; Aswin Akbar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine how the effect of profitability, liquidity, BOPO and working capital structure on the value of Islamic banking companies. The sample of this study amounted to 9 Islamic banks that have been listed on the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK) and published their financial statements with a total of 54 observations. Sampling used purposive sampling method with data analysis using regression test and data processing using eviews 10. The results showed that partially profitability, liquidity, BOPO and working capital structure had a significant effect on firm value. Simultaneous, profitability, liquidity, BOPO and working capital structure also have a significant influence on firm value.